Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.2174/138161209788168173
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiota in Drug Response

Abstract: Higher organisms such as mammals exist in a symbiotic relationship with their gut microbiota, formed from a diverse and highly metabolically active consortium of species. The gut microbiota, in addition to their ability to process dietary derived material, are also capable of performing a range of biotransformations on xenobiotics, such as drugs and their metabolites, in ways that can affect absorption and bioavailability. The potential for the gut microflora to influence drug metabolism and toxicity in unexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
70
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 28 publications
0
70
0
1
Order By: Relevance
“…The intestinal microbiota also affects the host metabolism, providing additional enzymes and regulating the expression of genes involved in the utilization of carbohydrates and lipids, and in drugs bioconversion (16)(17)(18). The number of genes of the collective genome (microbiome) of the microbiota exceeds by far those of the human genome, encoding additional metabolic features (17,19).…”
mentioning
confidence: 99%
“…The intestinal microbiota also affects the host metabolism, providing additional enzymes and regulating the expression of genes involved in the utilization of carbohydrates and lipids, and in drugs bioconversion (16)(17)(18). The number of genes of the collective genome (microbiome) of the microbiota exceeds by far those of the human genome, encoding additional metabolic features (17,19).…”
mentioning
confidence: 99%
“…Notably, microbial CYPs are also of clinical importance due mainly to the metabolic capacity that exists in the microflora of the gut. Differences in the composition of these microbes can account for some of the intra-and interindividual differences in drug metabolism and can lead to unexpected metabolic outcomes [78,79]. Gut microflora have been implicated in the metabolism of a number of different drugs including sulfasalazine, sulfinpyrazone, metronidazole, digoxin, isosorbide, flucytosine, and levodopa [1,80].…”
Section: Overviewmentioning
confidence: 99%
“…Xu et al (15) suggested that the soy products produced via the gut microbiota affected the CYP isoenzymes responsible for estrogen hydroxylation. There are numerous other instances of effects of microbiota dietary-derived compounds modulating xenobiotic metabolizing systems (13).…”
Section: Microbiomes and Drug Metabolismmentioning
confidence: 99%